Application of micro algae in poultry nutrition; a review - Thapa, Puja (Journal of Agriculture and Natural Resources, 2020)
In this review, we unveil the the use of microalgae as a feed ingredient in poultry nutrition. Microalgae are small-sized algae, unicellular, photosynthetic aquatic plants which have been studied as a natural marine resource for a number of economically applications, including animal feed. They are introduced to poultry diets mainly as a rich source of n-3 long chain polyunsaturated fatty acids, including docohexaenoic and eicosapentaenoic acid, but they can also serve as a protein, microelement, vitamin and antioxidants source, as well as a pigmentation agent for skin and egg yolks. The majority of experiments have shown that microalgae, mainly Spirulina and Chlorella sourced as a defatted biomass from biofuel production, can be successfully used as a feed ingredient in poultry nutrition. They can have beneﬁcial effects on meat and egg quality, through an increased concentration of n-3 polyunsaturated fatty acids and carotenoids, and in regards to performance indices and immune function. Positive results were obtained when fresh microalgae biomass was used to replace antibiotic growth promoters in poultry diets. Because of their chemical composition, microalgae can be efﬁciently used in poultry nutrition to enhance the pigmentation and nutritional value of meat and eggs, as well as partial replacement of conventional dietary protein sources.